2021
DOI: 10.1002/ejp.1765
|View full text |Cite
|
Sign up to set email alerts
|

'Reassurance and healthcare seeking in people with persistent musculoskeletal low back pain consulting orthopaedic spine practitioners: A prospective cohort study'

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…In practice, only a minority of patients consulting orthopaedic spine clinics in the UK enter their specialist consultation without imaging results. 5 For this group, reduction in imaging might be carried out through effective triage, to ensure that the majority of people turning up for surgical consultations were indeed surgical candidates. The overall message from clinicians was that people with PMLBP were not a good 'fit' to what they had to offer, and at least in part, a solution would be to ensure that they saw someone else.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In practice, only a minority of patients consulting orthopaedic spine clinics in the UK enter their specialist consultation without imaging results. 5 For this group, reduction in imaging might be carried out through effective triage, to ensure that the majority of people turning up for surgical consultations were indeed surgical candidates. The overall message from clinicians was that people with PMLBP were not a good 'fit' to what they had to offer, and at least in part, a solution would be to ensure that they saw someone else.…”
Section: Discussionmentioning
confidence: 99%
“…4 A recent longitudinal study in six UK hospitals found that around one in five patients consulting for back pain would be offered surgery. 5 Although imaging should only be indicated for patients with 'red flags', [6][7][8] in the UK it is common practice for the majority of patients consulting orthopaedic spine clinicians to receive an MRI scan. 5 For people with PMLBP, imaging often reveals signs of degeneration 9 10 which can also be observed in asymptomatic people.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations